Associations of device‐measured sleep, sedentariness and physical activity with growth differentiation factor 15 in older adults. Issue 2 (7th February 2022) - Ortolá, Rosario; García‐Esquinas, Esther; Buño‐Soto, Antonio; Cabanas‐Sánchez, Verónica; Martínez‐Gómez, David; Sotos‐Prieto, Mercedes; Struijk, Ellen A.; Caballero, Francisco Félix; Lopez‐Garcia, Esther; Banegas, José R.; Rodríguez‐Artalejo, Fernando
Abstract: Background: Growth differentiation factor 15 (GDF‐15) is a biomarker for chronic disease burden that might explain the health effects of sedentary behaviours (SBs) and physical activity (PA). We examined associations of device‐measured sleep, SB and PA, and time reallocations among them, with GDF‐15 in older adults. Methods: We used data from 2245 older adults participating in the Seniors‐ENRICA‐2 study. Wrist‐worn accelerometers were employed to ascertain total time in sleep, SB, light PA (LPA) and moderate‐to vigorous PA (MVPA). Associations between these activities and serum GDF‐15 levels were analysed using linear regression, including isotemporal substitution models for time reallocations among activities, and adjusted for potential confounders. Analyses were conducted separately in two groups (less active and more active individuals) according to the median total PA time. Results: In the less active participants, 30 min/day more of MVPA were related to lower levels of GDF‐15 when replacing sleep (fully adjusted mean percentage differences [95% confidence interval] in GDF‐15 of −9.2% [−13.2, −5.0]), SB (−9.8% [−13.6, −5.8]) and LPA (−5.8% [−11.1, −0.3]), whereas 30 min/day more of LPA were related to lower GDF‐15 when replacing both sleep (−3.6% [−6.1, −1.0]) and SB (−4.2% [−6.7, −1.7]). In the more active participants, 30 min/day more of MVPA were also associated with lower GDF‐15 when replacing sleep (−2.9% [−5.3, −0.3]), SB (−2.4% [−4.6, −0.2]) and LPA (−3.5% [−6.6, −0.3]), but no associations were found for more time in LPA. Spending more time in SB was associated with higher GDF‐15 levels only among those less active (1.9% [0.9, 2.9] per 30 min/day increment). Sleep time did not appear to be associated with GDF‐15. Conclusions: The MVPA was inversely associated with GDF‐15, with stronger associations at lower PA volumes. Also, more LPA and less SB time were linked to lower GDF‐15 in the less active individuals. This suggests that simply moving more and sitting less may reduce chronic disease burden in older adults.